2002
DOI: 10.1023/a:1015595100145
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Using a genomic clone encoding a rice lipid transfer protein, LTP1, we analysed the activity of the 5' region of the Ltp1 gene in transgenic rice (Oryza sativa L.) during plant development and under pathogen attack. The -1176/+13, -556/+13 and -284/+13 regions of the promoter were fused upstream from the uidA reporter gene and nos 3' polyadenylation signal, resulting in the pdelta1176Gus, pdelta556Gus and pdelta284Gus constructs which were transferred to rice by microprojectile bombardment. Histochemical and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Consequently, it would be very surprising to find a single nsLTPs in vivo function. Indeed, some nsLTPs have shown antimicrobial activity in vitro and the expression of their encoding genes is induced after pathogen infection, suggesting that they could be involved in defense against these invaders (Molina and García-Olmedo, 1993, 1997; Guiderdoni et al, 2002; Gomès et al, 2003). For those nsLTPs their defensive role would be acting like toxic weapons, but for the Arabidopsis DIR1 (defective in induced resistance1) nsLTP it would be carrying, or chaperoning, a still unknown systemic signal that triggers defensive responses in parts of the plant still free of the pathogen (Maldonado et al, 2002; Champigny et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it would be very surprising to find a single nsLTPs in vivo function. Indeed, some nsLTPs have shown antimicrobial activity in vitro and the expression of their encoding genes is induced after pathogen infection, suggesting that they could be involved in defense against these invaders (Molina and García-Olmedo, 1993, 1997; Guiderdoni et al, 2002; Gomès et al, 2003). For those nsLTPs their defensive role would be acting like toxic weapons, but for the Arabidopsis DIR1 (defective in induced resistance1) nsLTP it would be carrying, or chaperoning, a still unknown systemic signal that triggers defensive responses in parts of the plant still free of the pathogen (Maldonado et al, 2002; Champigny et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…9,17 Furthermore, the nsLTP genes from some plants are expressed in the leaf epidermal cell layer, where the waxy cuticle is generally found. 9,18 However, more complex expression profiles from individual experiments are frequently observed, such as expression in the xylem, phloem, or stigma, which can lead to disparate and unpredictable gene functions of nsLTPs. 1113 …”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that LTP expression is responsive to environmental stresses including salt, drought, cold treatment (Vignols et al, 1997;Arondel et al, 2000;Yubero-Serrano et al, 2003;Jung et al, 2006;Kim et al, 2006), and treatment with signaling molecules such as abscisic acid (ABA), salicylic acid (SA), ethylene, and methyl jasmonate (Vignols et al, 1997;Garcia-Garrido et al, 1998;Jung et al, 2006;Kim et al, 2006). Expression of LTP is protective against fungal and viral infection (Garcia-Olmedo et al, 1995;Blilou et al, 2000;Guiderdoni et al, 2002;Park et al, 2002;Jung et al, 2006;Kim et al, 2006;Chassot et al, 2007). It has been reported that LTP is involved in long-distance signaling during acquisition of systemic acquired resistance (SAR) in Arabidopsis thaliana (Maldonado et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The differential expression of three LTP genes, representing classes I, II, and III, in response to salt, ABA, and SA was analyzed using germinated seeds and young plants (Vignols et al, 1997;Kim et al, 2006). Inoculation with the fungal agent of the rice blast disease, Magnaporthe grisea, caused strong accumulation of transcripts of the class I LTP gene during the early hours of infection (Guiderdoni et al, 2002;Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%